Media Literacy Level and Violence Exposure Among Junior High School Students: A Pre-Post Descriptive Survey of a Social Intervention - Anita Amaliyah; Anisa Setya Arifina; Heni Indrayani (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
This study examines media literacy levels and violence exposure among eighth-grade students prior to a socialization intervention, and describes changes in comprehension, attitude, and practical knowledge following the program. Employing a pre-post descriptive survey design, data were collected from 32 students of class VIII B at SMP Negeri 1 Mertoyudan, Magelang, before a socialization program titled 'Bijak Menonton, Bijak Bertindak' (Watch Wisely, Act Wisely), and from 31 students in a post-socialization questionnaire. Pre-socialization findings revealed that 93.8% of students owned personal smartphones, 59.4% used them for three or more hours daily, and TikTok was the dominant platform. While 56.3% encountered violent or negative content at least occasionally, only 21.9% formally identified themselves as violence victims and despite behaviourally reported victimization rates being substantially higher. Media literacy was limited where only 43.8% of students reported knowing appropriate digital response steps. Following the socialization, which used the KPH (Kenali–Pahami–Hindari) framework with animated video, structured presentation, and a gamified quiz, it showed over 90% of students recognized victimization signs, over 85% knew appropriate responses to negative social media content, and the majority reported increased caution in interpersonal and online conduct. These findings highlight the persistent gap between violence experience and recognition, and demonstrate that interactive, framework-based media literacy socialization can meaningfully improve adolescent violence literacy in a single session.